The crisis of bourgeois domination in Brazil : How Polop interpreted Jânio Quadros and João Goulart governments (1961-1964) - Noberto, Lineker (Latitude, 2024)
Born in 1961 and opposing the reading produced by the Communist Party of Brazil (PCB) about the national reality, the Marxist Revolutionary Organization - Worker Policy (ORM-PO or Polop) presented an alternative political strategy to the pecebistas at the time. Despite the recognition that the specialized literature has already been expressing about its innovative role, the history of Polop remains little studied. This article intends to cover part of this gap, demonstrating the interpretation that the organization produced about Jânio Quadros and João Goulart governments and the serious political crisis that preceded the 1964 coup.